The On the Poetics of Fire between Bachelard and the Image of Burning the House by Barba - Salonna-Rogozińska, Ilaria (Załącznik Kulturoznawczy, 2019)
Burning the House is the title of Barba’s book on directing and dramaturgy. This expression has a symbolic meaning, although this meaning doesn’t find an explicative description in Barba’s words. In the paper, we are attempting an explanation of the idea of Burning the House in relation with theatre while also exploring the use of various images of fire present in the last book by Barba (and Savarese): The Five Continents of Theatre: Facts and Legends about the Material Culture of the Actor. In this work, the idea of Burning the house is the hidden leitmotiv in the whole composition of the book.